2015
DOI: 10.1038/gim.2014.97
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional aggressiveness of cerebral cavernous malformation disease associated with PDCD10 mutations

Abstract: Purpose The phenotypic manifestations of cerebral cavernous malformation (CCM) disease caused by rare PDCD10 mutations have not been systematically examined, and a mechanistic link to Rho kinase (ROCK) mediated hyperpermeability, a potential therapeutic target, has not been established. Methods We analyze PDCD10-siRNA treated endothelial cells for stress fibers, ROCK activity and permeability. ROCK activity is assessed in CCM lesions. Brain permeability and CCM lesion burden is quantified, and clinical manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
159
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 40 publications
(64 reference statements)
9
159
1
Order By: Relevance
“…This hyperpermeability is associated with RhoA kinase (ROCK) activation, and can be rescued by ROCK inhibition. 3,6,7 We also showed hyperpermeability to Evans blue dye in vivo in the brain and lungs of Ccm1 haploinsufficient mice, also rescued by ROCK inhibition. 3 The ROCK activity has been linked to increased CCM lesion burden in mice, and ROCK inhibition is being tested as a potential therapy to prevent CCM lesion development.…”
Section: Introductionmentioning
confidence: 63%
“…This hyperpermeability is associated with RhoA kinase (ROCK) activation, and can be rescued by ROCK inhibition. 3,6,7 We also showed hyperpermeability to Evans blue dye in vivo in the brain and lungs of Ccm1 haploinsufficient mice, also rescued by ROCK inhibition. 3 The ROCK activity has been linked to increased CCM lesion burden in mice, and ROCK inhibition is being tested as a potential therapy to prevent CCM lesion development.…”
Section: Introductionmentioning
confidence: 63%
“…Features of acute clinical aggressiveness included a demonstrated lesional growth or a symptomatic hemorrhage in the preceding year, or new lesion formation on comparable MRI image sequences in the preceding year in familial cases. Given the small numbers of cases with each disease aggressiveness feature, and the known correlation among the different features (i.e., patients with earlier symptom onset are more likely to experience greater lesion burden and multiple hemorrhages, patients with recent hemorrhage are more likely to experience recent lesional growth) [3], we subsequently considered the respective features of disease aggressiveness in chronic or acute domains for our primary hypothesis testing. Since CCM disease beginning in pediatric patients has been shown to be more severe than when disease onset is in adults [3,[5][6][7], we used symptoms beginning at or before 18 years of age as a feature of chronic disease aggressiveness.…”
Section: Extraction Of Clinical Parameters Definitions and Categorizatmentioning
confidence: 99%
“…A relevant disease biomarker might reflect chronic disease aggressiveness over the patient's lifetime, or more acute clinical activity [3,9,14]. We considered validated features of chronic disease aggressiveness including a history of multiple adjudicated clinically overt hemorrhages, early age of clinical onset or high lesion burden in familial cases.…”
Section: Extraction Of Clinical Parameters Definitions and Categorizatmentioning
confidence: 99%
See 1 more Smart Citation
“…In another multicenter study it was reported a very aggressive profile of FCCM cases due to mutations of the gene CCM3 22 , with a mean age at presentation of 12 years and an excessive lesion burden, meaning 33% of the patients having more than 100 lesions and 78% with more than 20 lesions. Epilepsy was also the most common symptom of this aggressive form of the disease.…”
Section: Familial Cerebral Cavernous Malformations (Fccm)mentioning
confidence: 99%